Six-membered ring systems: with O and/or S atoms - Santos, Clementina M.M. (2020)
A large variety of publications involving O- and S-6-membered ring systems have appeared in 2018. The importance of these heterocyclic compounds is highlighted by the large number of publications on the total synthesis of natural oxygen derivatives and of other communications dedicated to natural and synthetic derivatives. Reviews on the ruthenium-catalyzed synthesis of various O-6-membered heterocycles (18SC1551), the enantioselective syntheses of 3,4-dihydropyran derivatives (18CR2080), and strategies for the synthesis of coumarins (18SC1534) have appeared. The synthesis of natural pyran-2-ones and pyran-4-ones starting from alkynes and promoted by gold complexes (18AGE4215) and cyclization strategies of substituted alkynyl acids and esters to afford pyran-2-one and isocoumarin derivatives (18SL1) have been detailed in minireviews. The synthesis of various O-6-membered derivatives was also achieved through ultrasound irradiation (18SC1235) and using 4-hydroxy-6-methylpyran-2-one as a building block in multicomponent reactions (18H(96)381).